Lectotypification of Allium perdulce (Amaryllidaceae) - Svoboda, Harlan T.; Mayfield, Mark H. (Phytotaxa, 2020)
While verifying the status of alleged type specimens in the holdings of the U.S. National Arboretum Herbarium (NA; herbarium codes following Thiers [2020]), the first author (HTS) discovered a specimen of Allium perdulce S.V.Fraser (1939: 124), the gathering “Fraser 72,” that had several contradictory type annotations on the sheet. Additional study of the label and the protologue revealed that the specimen at NA was not a single gathering, as defined by the International Code of Nomenclature (Turland et al. 2018; Art. 8.2), but rather a mixed collection from different dates and locations. The protologue of A. perdulce states that the type specimen was deposited in the herbarium at Kansas State University (KSC) with “cotypes” being sent to GH, US, and NA, but no additional information about the type collection was provided. Thus, type material was sought at KSC to verify if the specimen at NA was in fact part of the type collection.